2006
DOI: 10.1677/joe.1.06365
|View full text |Cite
|
Sign up to set email alerts
|

Androgen inactivation and steroid-converting enzyme expression in abdominal adipose tissue in men

Abstract: We examined 5a-dihydrotestosterone (5a-DHT) inactivation and the expression of several steroid-converting enzymes with a focus on aldoketoreductases 1C (AKR1C), especially AKR1C2, in abdominal adipose tissue in men. AKR1C2 is mainly involved in the conversion of the potent androgen 5a-DHT to its inactive forms 5a-androstane3a/b,17b-diol (3a/b-diol). Subcutaneous (s.c.) and omental (Om) adipose tissue biopsies were obtained from 21 morbidly obese men undergoing biliopancreatic derivation surgery and 11 lean to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 51 publications
6
56
0
Order By: Relevance
“…Hence, if AKR1C3 is primarily expressed in fully matured adipocytes, the lower expression in adipose tissue from obese subjects with the metabolic syndrome could reflect a larger proportion of immature adipocytes in the sc adipose tissue. Several studies have reported a depot difference in AKR1C3 expression, with sc adipose tissue displaying the highest expression [12][13][14][15]. Our study expands on these findings by showing that AKR1C3 has the highest expression levels in sc adipose tissue when compared with 64 other human tissues.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Hence, if AKR1C3 is primarily expressed in fully matured adipocytes, the lower expression in adipose tissue from obese subjects with the metabolic syndrome could reflect a larger proportion of immature adipocytes in the sc adipose tissue. Several studies have reported a depot difference in AKR1C3 expression, with sc adipose tissue displaying the highest expression [12][13][14][15]. Our study expands on these findings by showing that AKR1C3 has the highest expression levels in sc adipose tissue when compared with 64 other human tissues.…”
Section: Discussionsupporting
confidence: 79%
“…5. As in previous studies [12][13][14][15], omental adipose tissue displayed a lower expression level than sc adipose tissue.…”
Section: Akr1c3 Is Highly Expressed In the Sc Adipose Tissue Depotsupporting
confidence: 82%
See 2 more Smart Citations
“…Adipose tissue is now considered as an important endocrine organ, which is a major site for metabolism of sex steroids (Kershaw & Flier 2004, Blouin et al 2006) and interestingly, the retroperitoneal fat Figure 1 Amino acid sequence comparison of the mouse, human, and monkey 17b-HSD12 and 17b-HSD3. The amino acid sequences of the mouse 17b-HSD12 and 17b-HSD3 are aligned with their primate homologs.…”
Section: Discussionmentioning
confidence: 99%